Capital gains taxation under different tax regimes - Caren Sureth; Dirk Langeleh (Arbeitskreis Quantitative Steuerlehre (arqus), 2005)
This paper investigates the influence of different systems of current income and capital gains taxation on investor's decision to either carry out an investment in corporate shares or to invest funds alternatively on the capital market. Three basic tax systems are analyzed, a classical corporate tax system with double taxation of profits on corporate and personal level, a shareholder relief system, that reduces double taxation completely. It can be shown that general analytical solutions for the investment problem for different categories of tax regimes, even under certainty, cannot be derived. Applying a growth model, we find under rather restrictive assumptions that the shareholder relief system invokes more severe distortions than the full imputation system. Trying to prove this in a more realistic setting with uncertainty we employ Monte Carlo Simulation for random rates of return and random income tax rates. In many cases, the degree of tax-induced uncertainty is significantly lower under a shareholder relied system than under full imputation. Furthermore, it can be shown that under uncertainty full imputation causes more severe distortions than shareholder relief whenever personal income tax rates are low. In light of international tax competition this is an important result as a reduction of tax rates is taking place or is likely to take place in several countries. Furthermore, the simulation clarifies the trade-off of the opposing effects, i.e. tax and interest rate effects, and the overwhelming impact of capital gains taxation. Apart from tax parameters, we identify the dividend rate and the point in time of selling the shares as important value drivers.
Keywords: H25; H21; 330; capital gains taxation; dividend policy; tax neutrality; timing decisions; Wertzuwachssteuer; Steuersystem; Steuerwirkung; Betriebliche Investitionspolitik; Dividende; Betriebliche Terminplanung; Besteuerungsgrundsatz; Theorie